2016
DOI: 10.1007/s10389-016-0738-3
|View full text |Cite
|
Sign up to set email alerts
|

Wealth index, empowerment and modern contraceptive use among married women in Nigeria: are they interrelated?

Abstract: Background Nigeria, a patriarchal society, is one of the more impoverished countries of the world and while its fertility and population growth rates are high, its modern contraceptive (MC) prevalence rate is low. The wealth status and decisionmaking power of a woman have implications on their use of MC. Studies that examined the relationship between women's empowerment, wealth index and MC use in Nigeria are scarce. Methods A national representative cross-sectional data on women of reproductive age (n = 5,098… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
15
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 9 publications
(10 reference statements)
12
15
2
Order By: Relevance
“…A woman who resides in the Afar and Somali region of Ethiopia was nearly 55 and 93% times less likely to utilize modern contraceptive methods as compared to a woman residing in Addis Ababa. The finding is consistent with the results of secondary data analysis of the 2013 Nigerian Demographic and Health Survey (NDHS) [19,25] analyzed by independent researchers.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A woman who resides in the Afar and Somali region of Ethiopia was nearly 55 and 93% times less likely to utilize modern contraceptive methods as compared to a woman residing in Addis Ababa. The finding is consistent with the results of secondary data analysis of the 2013 Nigerian Demographic and Health Survey (NDHS) [19,25] analyzed by independent researchers.…”
Section: Discussionsupporting
confidence: 89%
“…Urban women are more educated, have better income, have better access to the health facility, and better media access than rural women which have a positive impact on modern contraceptive utilization. Rural women also need more children to help them with fieldwork which has a negative effect on their modern contraceptive method utilization [14,19,21,23,25,26]. But the result of secondary data analysis of the 2003-2014 Ghana Demographic and Health Surveys showed that rural resident women more likely utilized modern contraceptive methods than urban resident women which are in contrary to the results of the current study [17].…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…High household wealth was positivly associated with modern contraceptive utilization those young women in poorest household were less likely to use modern contraceptive when compared to richest household. It is comparable to study conducted in Tanzania and Nigeria (47,48). The possible explanation could be related to the implicit costs needed to access health care services, mass media and education, as well wealthier background ought to have better decision making power on contraceptive use (44) .…”
Section: Geographical Variation and Clustering Of Modern Contraceptivsupporting
confidence: 65%
“…Several studies have recorded higher contraceptive use among women with the richest wealth quintile compared to the poorest 6,9,[11][12][13] . The use of modern contraceptives has been reported to be higher among the highly empowered and the upper class women compared to the poorly empowered and lower class women 14 . Strategies to improve contraceptive uptake should therefore focus more on the latter group of women.…”
Section: Introductionmentioning
confidence: 99%